Thesis Title Terms of reference of the metaphor in the Modern European painting (Analytical study) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2021)
The current study looks forward to understand Terms of reference of the metaphor in the Modern European painting which are represented by form and its and its indicative system which has participated in Fine Arts and the development depending on previous metaphor related to the modernization .So , accordingly , thesis has included four parts , the first chapter has included the frame of approach . To offer he problem of thesis and its importance with the objects of time and subjective one , in addition to identifying the basic idioms in thesis.Chapter Two has contained the theoretical frame which has included two main topics , the first one has dealt with employing the formative and the indicative metaphor in the Modern European painting , the second topic has concerned with studying the features and the characteristics of modernity and has meant in studying attributes of modernity between concept and meaning in modern European painting. As well as the theoretical framework indicators. And ensure that Chapter III had concerned with research procedures, which contained the research of community and the research of methodology and research of tool. Then , the researcher has analyzed (three samples) of European artists to gain access to the research results within the fourth chapter which included: 1-One important figure in modern European painting follow the kind of interpretation, through changing the offset that achieve some kind of formal and semantic employment, with the help of imagination mental process of the image.2-The emergence of innovative forms of its predecessor without moving them directly, derived from the past and reformulate some of the characteristics of formal and semantic, of the terms of reference of knowledge, so that metaphor reference resulting from the understanding of the impact experience, on the grounds that the metaphor of creative feature technical result of a sophisticated awareness owned by the artist. The researcher has reached the conclusions of display including the following:1- A European artist was credited with building the technical bridge the link between the world's arts, within the first foundation stages, of the characteristics of modern composition, especially in the art of drawing, through the mechanisms adopted in the construction of forms and methods of technical Manifesting in formulations of color which, with abstract features, derived from borrowed configurations that characterized feature abstraction.